IDENTIFICATION OF RIFAMPICILIN-RESISTANT MYCOBACTERIUM TUBERCULOSIS STRAINS BY POINT MUTATION ANALYSIS OF RPOB GENE - Minh, Nghiêm Ngọc (Vietnam Journal of Biotechnology, 2011)
Mycobacterium tuberculosis (MTB) is a pathogenic baterial species in the genus of Mycobacterium causing most cases of tuberculosis. As reported by WHO tuberculosis threatens the health of one third of the world’s population. The most facing problem which makes tuberculosis become more seriously is the appearance of antibiotic-resistant TB strains classified as Multi-drug Resistant TB (MDR-TB), Extensively Drug Resistant (XDR) and TB co-infected with HIV/AIDS. Screening and detection drug-resistant strains would help the treatment and diagnosis for tuberculosis more effective in patients. Advantages in molecular biological techniques such as PCR, real-time PCR allow researchers rapidly, exactly identity the drug-resistant M.tuberculosis strains isolated from patients. In this study, primer pairs rpoB-F and rpoB-R were designed to amplify the rifampicin resistance determining region (RRDR) including 27 codon of the rpoB gene. After amplified sequences of Mycobacterium tuberculosis strains isolated from 7 patients of the central hospital in Hue, the were forwarded for sequencing. The Results of sequence analysis showed that a mutation at the codon 531 detected. And this result was useful method to change the treatment for these patients.